Effects of genotype and Phytolacca dodecandra (Endod) supplementation on growth performance, carcass traits, blood profiles, and breast meat quality of chickens - Tadele, A.; Berhane, G.; Esatu, Wondmeneh; Kebede, F.; Wassie, T. (Elsevier, 2024)
In this study, we investigated the effects of genotype and Phytolacca dodecandra (Endod) supplementation on the growth, carcass traits, blood profiles, and breast meat quality of chickens. The study lasted for 18 weeks and involved 360 unsexed day-old chicks divided into nine groups with 40 chicks each, replicated four times with 10 chicks per replication. The genotypes studied were Naked-neck * Tetra H, Normal-feathered * Tetra H, crosses and Tetra H * Tetra H, while the diets included a standard commercial ration (C), Phytolacca dodecandra (Endod) at 1 g/kg (C+1), and Phytolacca dodecandra (Endod) at 2 g/kg (C+2). Results showed that both diet and genotype influenced growth performance indicators like final body weight, body weight change, average daily gain, and feed conversion ratio, particularly during the grower and entire phases. When compared to the control diet, the Phytolacca dodecandra (Endod) chicks supplemented at 1 g/kg showed better performances. The genotypes also affected dressing percentage, breast, thigh, keel bone, and gizzard components, with higher values found in the Naked-neck by Tetra H cross. The supplemented chicken group exhibited an improvement in the dressing percentage and breast muscle in comparison to the control. Blood parameters were also significantly influenced (P < 0.01) by genotype, diet, and their interaction. Supplementation significantly (P < 0.01) increased protein levels while reducing the cholesterol and triglyceride levels in the blood. Incorporating Phytolacca dodecandra (Endod) at a rate of 1 g/kg into the diet of chickens brought a significant improvement in the protein content, and a reduction in the fat content, of their breast muscles. In general, the study indicates that adding up to 2 g/kg of Phytolacca dodecandra (endod) to chicken feed enhances growth performance traits, carcass traits, blood profiles, and breast muscle protein levels, without any negative consequences.